Pendampingan UMKM dan Pengembangan Greenhouse: Program Pengabdian Masyarakat Untuk Meningkatkan Kualitas Hidup Pelaku Usaha dan Petani di Desa Sukowati Bojonegoro - Rizka Damayanti; Dewi Rochmayanti; Raihan Anugerah Raganesa; Syaidatun Nisa; Yeti Afrinalita; Mei Rina Lestari; M. Jauharul Ma’arif; Devinta Bintang Safitri (Lembaga Pengembangan Kinerja Dosen, 2025)
Sukowati Village faces significant challenges in the development of MSMEs and the management of greenhouse facilities, which include limited product marketing, lack of innovation in the design and diversification of MSME products, and suboptimal greenhouse conditions to support local agriculture. The Community Service Program is here to overcome this problem through digital marketing training, packaging design, and product diversification to increase the capacity of MSMEs, as well as greenhouse revitalization through infrastructure improvement and active community involvement in its management. As a result, MSMEs in Sukowati Village have succeeded in improving product quality, expanding market reach through digital platforms, and greenhouses now function optimally as centers for productive and educational agricultural activities. This strategic approach creates a sustainable positive impact, strengthens the foundations of the local economy, and becomes an effective model of community empowerment for regions with similar challenges, while improving community well-being in a sustainable manner.